EFEKTIVITAS PEMBELAJRAN BERBASIS PROYEK (PROJECT BASED LEARNING) TERHADAP HASIL BELAJAR MATA KULIAH EKONOMI KREATIF - Lubis, Putri Kemala Dewi; Revita Yuni; Khairani Alawiyah Matondang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The curriculum applied in the Bachelor of Economics Education study program at Medan State University uses the concept of Independent Learning with an output-oriented approach or Outcome-Based Education (OBE). In this output-based approach, results in the form of knowledge and skills must be measurable concretely. To achieve optimal measurement results, it is necessary to apply a project-based learning model that is in accordance with OBE principles in the study program. This OBE-based PJBL model is expected to be able to improve students' abilities as reflected in the achievement of their learning outcomes. This research uses research and development (R&D) methods, with a development model adapted from the ADDIE model. Based on the research results, 96.7% of students got an A grade, while 3.3% got an E grade. This shows that the PjBL model is very effective in improving student learning outcomes, especially in Creative Economy courses.